Analisis Wujud dan Maksud Implikatur dalam Novel Guru Aini Karya Andrea Hirata - Sri Yanti (Universitas Indraprasta PGRI, 2021)
Novels can be studied pragmatically, especially from the implicature aspect. The method used in this research is a qualitative descriptive method supported by a pragmatic approach specifically regarding implicatures. The population of this research is the utterances of the characters in the novel Guru Aini by Andrea Hirata. There is also a sample of this study consisting of 76 character utterances that contain implicatures. The sampling method uses random techniques. The theory used in the analysis is the theory of George Yule (2014). The findings of this study are First, the form of the implicature is based on the communicative function and the form of grammatical construction. The form of the implicature is divided into two, namely conventional and conversational implicatures. Conversational implicature is divided into three, namely general conversation, scale and special conversation. The form of a special conversation is divided into declarative, interrogative and imperative. Second, the meaning of the implicature is based on the form of the implicature. Keywords: Novel; Form of Implicature; Implicature Intent.